Work-Family Conflict, Environment, Stress, and Employee Burnout in Hospitality: Dampak Konflik Kerja-Keluarga, Lingkungan Kerja, dan Stres Kerja terhadap Burnout Karyawan: Studi Kuantitatif di Sektor Perhotelan - Tegar Bagas Oktavian Haidar; Rifdah Abadiyah (Universitas Muhammadiyah Sidoarjo, 2022)
This research investigates the relationship between work-family conflict, work environment, work stress, and employee burnout in the context of High Point Apartment Surabaya. The study aims to explore the extent to which these factors contribute to burnout among employees. A quantitative research approach was employed, utilizing a questionnaire-based survey. The sample comprised 40 employees from High Point Apartment Surabaya, and data analysis was conducted using SPSS statistical software version 2.5.0. The findings reveal that work-family conflict, work environment, and work stress significantly influence employee burnout. These results emphasize the importance of addressing these factors to mitigate burnout and enhance employee well-being in the hospitality industry. This study contributes to the existing literature on burnout by shedding light on its underlying causes in the specific context of High Point Apartment Surabaya, offering implications for organizations and providing valuable insights for researchers in the field of occupational health and psychology. Highlights: Work-family conflict: Investigating the influence of conflicts between work and family responsibilities on employee burnout in the hospitality sector. Work environment: Examining the impact of the work environment on employee burnout in the context of High Point Apartment Surabaya. Work stress: Assessing the significance of work-related stressors in contributing to employee burnout among hospitality professionals. Keywords: Employee burnout, Work-family conflict, Work environment, Work stress, Hospitality sector.